ANALISIS FRAMING PEMBERITAAN PEMBANGUNAN POJOK DILAN PADA MEDIA PIKIRAN-RAKYAT.COM.COM DAN NEWS.DETIK.COM/JAWABARAT - Muzakkir, Musniyah Ayunita; Fitriawan, Rana Akbari (Jurnal Common, 2020)
The establishment of the Dilan’s Corner became an issue that caused a pros and cons polemic among the people of Bandung City. Because there is news value from this Dilan’s Corner establishment issue, local media such as pikiran-rakyat.com.com and news.detik.com/jawabarat raised this news. These two media certainly have differences in constructing existing reality. This study aims to determine how the online media, pikiran-rakyat.com.com and news.detik.com/jawabarat framing news related to the construction of Dilan’s Corner in Bandung using the framing model of Zhondang Pan and Gerald M. Kosicki. In this study, qualitative research methods with a constructionist paradigm are used. The results of this study are different news framing from the two media. Pikiran-rakyat.com.com tends to highlight the main resource person, Ridwan Kamil as the Governor of West Java as well as the initiator of Dilan Corner so that the alignments can be seen from pikiran-rakyat.com.com, while news.detik.com/jawabarat seems to be more taking sides in the public interest that is marked by the selection of varied and inclined sources to show their resistance to the Dilan’s Corner establishment.